2022
DOI: 10.21037/atm-22-1165
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between the gut microbiome and clinical response in locally advanced thoracic esophageal squamous cell carcinoma during neoadjuvant camrelizumab and chemotherapy

Abstract: Background:The gut microbiome is associated with the response to immunotherapy in a variety of advanced cancers. However, the influence of the gut microbiome on locally advanced esophageal squamous cell carcinoma (ESCC) during programmed cell death protein 1 (PD-1) antibody immunotherapy plus chemotherapy is not clearly demonstrated. To explore the crosstalk between the gut microbiome and clinical response in locally advanced thoracic ESCC during neoadjuvant camrelizumab and chemotherapy Methods: Patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…26 Given that some patients with low PD-L1 expression experience clinically meaningful benefit, there is a need to explore additional predictive biomarkers, such as tumor mutational burden, immune signatures, and gut microbiota, which may need to be used in tandem with PD-L1 to identify responders. [27][28][29] Clinicians should be aware of the differences between the TPS and CPS as methods of measuring PD-L1 expression. Recent work 30 has suggested that PD-L1 expression fluctuates temporally by site of tumor biopsy or prior chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Given that some patients with low PD-L1 expression experience clinically meaningful benefit, there is a need to explore additional predictive biomarkers, such as tumor mutational burden, immune signatures, and gut microbiota, which may need to be used in tandem with PD-L1 to identify responders. [27][28][29] Clinicians should be aware of the differences between the TPS and CPS as methods of measuring PD-L1 expression. Recent work 30 has suggested that PD-L1 expression fluctuates temporally by site of tumor biopsy or prior chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…microbiota, which may need to be used in tandem with PD-L1 to identify responders. [27][28][29] Clinicians should be aware of the differences between the TPS and CPS as methods of measuring PD-L1 expression. Recent work 30 has suggested that PD-L1 expression fluctuates temporally by site of tumor biopsy or prior chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of circulating tumor DNA (ctDNA) to assess MRD shows promise in screening suitable populations for postoperative adjuvant therapy and consolidation therapy after definitive chemoradiotherapy ( 102 105 ). Various molecular biomarkers have been identified to predict the response to neoadjuvant chemoradiotherapy for esophageal cancer, as well as various lymphocyte subsets and lymphocyte ratios in the peripheral blood/tumor area, dendritic cells, cytokines, and gut microbiota, have also been reported to have predictive value ( 35 , 44 , 106 110 ). However, these biomarkers are not yet widely utilized in clinical practice, and further research is required to determine whether they can predict the effectiveness of immunotherapy in combination with radiotherapy.…”
Section: Discussion: Current Progress and Future Directionmentioning
confidence: 99%
“…In recent years, neoadjuvant immunotherapy has emerged as a rapidly developing treatment option for cancer patients [ 79 ]. Xu et al found that taxonomic features of the gut microbiome can predict the pathological response and severe adverse events (≥ 3 grade) in esophageal squamous cell carcinoma (ESCC) patients who were undergoing neoadjuvant camrelizumab and chemotherapy [ 67 ], which further expands the potential applications for gut microbiome biomarkers.…”
Section: Prediction Of Iraes By Gut Microbiomementioning
confidence: 99%